2002
DOI: 10.1111/j.1749-6632.2002.tb04925.x
|View full text |Cite
|
Sign up to set email alerts
|

Results of Long‐Term Carcinogenicity Bioassays on Tert‐Amyl‐Methyl‐Ether (TAME) and Di‐Isopropyl‐Ether (DIPE) in Rats

Abstract: Tert-amyl-methyl ether (TAME) was administered by gavage in extra virgin olive oil solution at concentrations of 750, 250, or 0 mg/kg bw to groups of 100 male and 100 female Sprague-Dawley rats 8 weeks old at the start of the experiment. Di-isopropyl ether (DIPE) was administered in the same manner at the doses of 1000, 250, or 0 mg/kg body weight to groups of 100 male and 100 female Sprague-Dawley rats. TAME and DIPE were each delivered in 1-mL solution 4 days a week for 78 weeks. Control animals received 1 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 7 publications
0
11
0
1
Order By: Relevance
“…Finally, it should be noted that out of 49 agents reported to be carcinogenic in rats by the CMCRC/ERF, only 8 of these agents induced hemolymphoreticular malignancies. Of these, 3 were demonstrated in both males and females—formaldehyde (Soffritti et al 2002b), mancozeb (Belpoggi et al 2002a), and di-isopropyl-ether (Belpoggi et al 2002b)—and 5 only in females—toluene (Soffritti et al 2004), methyl alcohol (Soffritti et al 2002a), methyl tert -butyl ether (Belpoggi et al 1995), tert -amyl-methyl-ether (Belpoggi et al 2002b), and APM (Belpoggi et al 2006; Soffritti et al 2005, 2006). …”
Section: Discussionmentioning
confidence: 99%
“…Finally, it should be noted that out of 49 agents reported to be carcinogenic in rats by the CMCRC/ERF, only 8 of these agents induced hemolymphoreticular malignancies. Of these, 3 were demonstrated in both males and females—formaldehyde (Soffritti et al 2002b), mancozeb (Belpoggi et al 2002a), and di-isopropyl-ether (Belpoggi et al 2002b)—and 5 only in females—toluene (Soffritti et al 2004), methyl alcohol (Soffritti et al 2002a), methyl tert -butyl ether (Belpoggi et al 1995), tert -amyl-methyl-ether (Belpoggi et al 2002b), and APM (Belpoggi et al 2006; Soffritti et al 2005, 2006). …”
Section: Discussionmentioning
confidence: 99%
“…Two other ether-based additives, TAME (Fig. 2) and DIPE (Di-isopropyl ether) have been recently assessed for toxicity, and both were found to have a carcinogenic potential in rats, increasing tumor-forming rates in both female and male rats [110]. This study concluded a similar carcinogenic potential for both additives, however the exact concentrations for discerning between mutagenic and carcinogenic responses were not identified, and require further studies.…”
Section: Health and Environmental Hazards Of Ether-additivesmentioning
confidence: 86%
“…In a carcinogenicity study with rats diisopropyl ether was reported to be potential carcinogenic for various organs and tissues [48]. However, the study shows deficiencies in design and reporting, which made interpretation difficult.…”
Section: Toxicologymentioning
confidence: 99%